The Meaning of Michelle: 16 Writers on the Iconic First Lady and How Her Journey Inspires Our Own - Veronica Chambers (St. Martin's Press, 2017)
Michelle Obama is unlike any other First Lady in American History. From her first moments on the public stage, she has challenged traditional American notions about what it means to be beautiful, to be strong, to be fashion-conscious, to be healthy, to be First Mom, to be a caretaker and hostess, and to be partner to the most powerful man in the world. What is remarkable is that, at 52, she is just getting started.